2020
DOI: 10.1590/0103-6440202003376
|View full text |Cite
|
Sign up to set email alerts
|

A New Calcium Silicate-Based Root Canal Dressing: Physical and Chemical Properties, Cytotoxicity and Dentinal Tubule Penetration

Abstract: The aims of this study were to evaluate the physical and chemical properties, cytotoxicity and dentinal tubule penetration of a new calcium silicate-based root canal dressing. For pH and calcium ion release evaluation (1, 24, 72 and 168 h) were used a pH meter and colorimetric spectrophotometer, respectively. Radiopacity evaluation followed the ISO 6876:2012. Cytotoxicity was evaluated by the percentage of cell viability using MTT assay. Illustrative images of dentinal tubule penetration were obtained using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 22 publications
3
47
2
6
Order By: Relevance
“…In the present study, the null hypothesis was rejected, as significant differences were found between the calcium silicate‐based materials in most of the evaluated parameters. Although previous studies have evaluated BD using similar methodologies (Adl et al, 2019; Farrugia et al, 2018; Marconyak et al, 2015; Ochoa‐Rodrıguez et al, 2019; Ochoa‐Rodriguez et al, 2020; Oliveira et al, 2020; Shokouhinejad et al, 2016; Vallés et al, 2015; Yoldas et al, 2016), few studies have used BCT (Guerreiro et al, 2021; Oliveira et al, 2020; Villa et al, 2020) and BCR (Benetti et al, 2019; Ghilotti et al, 2020; López‐García et al, 2019), which are new ready‐to‐use materials. To assess crown discolouration by these materials in the presence of blood components, a model was designed to simulate the clinical situation of partial pulpotomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the null hypothesis was rejected, as significant differences were found between the calcium silicate‐based materials in most of the evaluated parameters. Although previous studies have evaluated BD using similar methodologies (Adl et al, 2019; Farrugia et al, 2018; Marconyak et al, 2015; Ochoa‐Rodrıguez et al, 2019; Ochoa‐Rodriguez et al, 2020; Oliveira et al, 2020; Shokouhinejad et al, 2016; Vallés et al, 2015; Yoldas et al, 2016), few studies have used BCT (Guerreiro et al, 2021; Oliveira et al, 2020; Villa et al, 2020) and BCR (Benetti et al, 2019; Ghilotti et al, 2020; López‐García et al, 2019), which are new ready‐to‐use materials. To assess crown discolouration by these materials in the presence of blood components, a model was designed to simulate the clinical situation of partial pulpotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Other ready‐for‐use silicate‐based materials developed recently are Bio‐C Temp (BCT; Angelus, Londrina, PR, Brazil) and Bio‐C Repair (BCR; Angelus). Both have low cytotoxicity (Ghilotti et al, 2020; Guerreiro et al, 2021; López‐García et al, 2019; Oliveira et al, 2020; Villa et al, 2020), good biocompatibility (Benetti et al, 2019) and biomineralization ability (Benetti et al, 2019; López‐García et al, 2019). BCT was primarily conceived by the manufacturer as an intracanal dressing (Villa et al, 2020) and is also indicated for full pulpotomy (Oliveira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Já o Bio-C Temp apresentou os menores valores de pH em todos os períodos experimentais com diferença significativa com os grupos HC/Soro e HC/PG (P < 0,05). Os materiais a base de silicatos de cálcio, quando hidratados, formam o hidróxido de cálcio que se dissociam rapidamente em íons Ca ++ e OHaumentando o pH do meio (Villa, et al, 2020). No entanto, a baixa solubilidade do HC pode ser responsável pela lenta liberação dos íons OH -, justificando os menores valores do pH do Bio-C Temp.…”
Section: Discussionunclassified
“…O crescente interesse por esses materiais é evidenciado pelo desenvolvimento de novos medicamentos bioativos à base de silicato de cálcio, como o Bio-C Temp (Angelus Indústria de Produtos Odontológicos S/A, Londrina, PR, Brasil). Esse medicamento se apresenta como uma pasta pronta para uso, é biocompatível, possui pH alcalino e boa radiopacidade (Villa, et al, 2020). Além disso, o Bio-C Temp induz a biomineralização e possui atividade antimicrobiana (Guerreiro, et al, 2021).…”
Section: Introductionunclassified